Improving The Ability Of Writing Shows Using The Scientific Learning Model In Class X Students Of SMK N 2 Hiliserangkai - Eperiani Mendrofa (Indonesian Journal of Education and Mathematical Science, 2021)
The purpose of this study was to determine the improvement in the ability to write short stories using the Scientific learning models in Class X Students of SMKN 2 Hiliserangkai. PTK (Classroom Action Research) models which consist of 4 stages, namely the planning, action, observation, and reflection stages.Sources of research data for class X students of SMKN 2 Hiliserangkai City were 28 people and the data of this study were short story texts. Data collection uses test instructions to write short stories with specified themes and student activity observation sheets. Data analysis uses average calculations and final analysis qualitatively. The results showed that there was an increase in short story writing skills through the scientific learning model for students of class X OTKP of SMKN 2 in Hiliserangkai. This is evident from the learning results in the first cycle obtained an average of 70.21 with good categories and increased in the learning outcomes of the second cycle with an average of 80.14 with a very good category. Student activities include aspects of discipline, responsibility, cooperation and independence with the category active enough in the first cycle to increase to be very active in the second cycle in the learning material describing the structure of the text, life values, and structure of short story builders.Keywords: Ability, writing, short story, scientific.